Simulations of the Light Scattering Properties of Metal/Oxide Core/Shell Nanospheres. (6th April 2014) - Ruffino, F.; Piccitto, G.; Grimaldi, M. G.
Abstract : Given the importance of the optical properties of metal/dielectric core/shell nanoparticles, in this work we focus our attention on the light scattering properties, within the Mie framework, of some specific categories of these noteworthy nanostructures. In particular, we report theoretical results of angle-dependent light scattering intensity and scattering efficiency for Ag/Ag2 O, Al/Al2 O2, Cu/Cu2 O, Pd/PdO, and Ti/TiO2 core/shell nanoparticles as a function of the core radius/shell thickness ratio and on a relative comparison. The results highlight the light scattering characteristics of these systems as a function of the radius/shell thickness ratio, helping in the choice of the more suitable materials and sizes for specific applications (i.e., dynamic light scattering for biological and molecular recognition, increasing light trapping in thin-film silicon, organic solar cells for achieving a higher photocurrent).